PENGARUH GROWTH OPPORTUNITY, LEVERAGE, KEPEMILIKAN MANAJERIAL, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Lidiya Yolanda; Sugeng Priyanto; Mia Laksmiwati; Dicky Arisudhana (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2024)
The aim of this research is to determine the influence of the variables growth opportunity, leverage, managerial ownership and profitability on earnings management. The population used in this research were industrial sector manufacturing companies listed on the Indonesia Stock Exchange and the research observation period was 2018 to 2022. The sample selection used was a purposive sampling method which was adapted to the objectives of the research problem. The number of samples used in the research was 18 from 56 companies. The data analysis method used in this research is multiple linear regression analysis using the SPSS version 26 program tool. The research results show that the growth opportunity and profitability variables have a significant influence on earnings management. Meanwhile, the leverage and managerial ownership variables have no effect on earnings management.